Circular Economy for Strategic Management in the Copper Mining Industry - Vargas-Norambuena, J (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This study examines the awareness and implementation of Circular Economy (CE) principles within Chile’s mining sector, which represents the world’s leading copper producer. We employed a mixed-methods approach, combining quantitative surveys with qualitative semi-structured interviews, to evaluate perceptions and implementation levels of CE practices across diverse organizational contexts. Our findings reveal a pronounced knowledge gap: while 73.3% of mining professionals reported familiarity with CE concepts, only 57.3% could provide accurate definitions. State-owned mining companies demonstrated substantially higher CE implementation rates, with 36.5% participating in eco-industrial collaborations and 51% conducting environmental audits, compared to their private counterparts. Small enterprises (1–100 employees) exhibited particularly limited engagement, as demonstrated by 71.8% lacking established sustainability reporting mechanisms. A considerable implementation gap was also identified; although 94.8% of respondents considered CE principles integral to business ethics and 89.6% recognized CE as essential for securing a social license to operate, only 20.8% reported that their organizations maintained dedicated CE units. The research presents actionable recommendations for policymakers, including targeted financial incentives and training programs for small- and medium-sized enterprises (SMEs) in mining services, the establishment of standardized CE performance metrics for the sector, and the integration of CE principles into strategic management education to accelerate sustainable transformation within Chile’s critical mining industry. © 2025 by the authors.